Simulation of Seismic Wave Propagation on Asteroid Ryugu Induced by The Impact Experiment of The Hayabusa2 Mission: Limited Mass Transport by Low Yield Strength of Porous Regolith. Issue 2 (23rd February 2021) - Nishiyama, G.; Kawamura, T.; Namiki, N.; Fernando, B.; Leng, K.; Onodera, K.; Sugita, S.; Saiki, T.; Imamura, H.; Takagi, Y.; Yano, H.; Hayakawa, M.; et al.
Abstract: Seismic shaking has been regarded as an essential source of resurfacing on asteroids. The Small Carry‐on Impactor (SCI) operation on Hayabusa2 has been expected to be a unique opportunity for testing in situ seismic shaking whose energy is sufficiently large to excite observable surface modification. However, no obvious regolith hopping was identified even immediately outside of the crater formed by the SCI impact. To understand this discrepancy from the expectation, we simulate seismic wave propagation on Ryugu with a wide range of surface material properties and evaluate maximum acceleration on the surface. Numerical results reveal that low‐quality factor or low seismic efficiency is required to explain the lack of geomorphological change after the SCI experiment. Considering that scattering under anhydrous conditions cannot efficiently dissipate energy, such a low‐quality factor is not plausible. The weak yield strength in porous materials can efficiently decrease seismic wave energies, making the apparent seismic efficiency extremely low. Based on this hypothesis, we propose a formulation of surface mobility on asteroids that considers the physical properties of regolith. We consistently estimate the occurrence of seismic shaking with the existence of unstable boulders on Ryugu. Plain Language Summary: The Japanese asteroid exploration mission, Hayabusa2, successfully performed an artificial impact cratering operation on April 5, 2019. Extensive surface modification was expected to be excited by the impact‐induced seismic waves; however, boulders stayed at almost the same location. We conduct seismic wave propagation simulations to resolve this apparent discrepancy and to understand the physical properties of Ryugu. We show that surface changes are strongly dependent on a shallow subsurface. Our results suggest that the conversion of impact energy to seismic waves is less efficient than previously thought. The weakness of powdery regolith may limit asteroid‐quakes at the surface. Based on this hypothesis, we propose a formulation how the surface moves on asteroids that considers the unclear properties of regolith. The lack of seismic shaking agrees with the mysterious discovery that boulders stay unstably on other boulders. Key Points: Unexpectedly little movement of boulders due to the Small Carry‐on Impactor impact experiment on Ryugu is investigated by seismic wave propagation simulation Low‐yield strength of asteroid regolith is likely to limit seismic wave amplitude Meteoroid impacts on small asteroids possibly cause seismic shaking, but its contribution to resurfacing is localized